Case Report: Hereditary neuropathy with liability to pressure palsy (HNPP): the role of genetic investigation in diagnostic assessment - Salvatore Savasta; Fabiola Serra; Lucrezia Galimberti; Francesco Fabrizio Comisi; Marcello Cossu; Alessandro Vannelli; Maddalena Masala; Sara Tanca; Stefania Murru (Frontiers in Genetics)
Hereditary neuropathy with liability to pressure palsies (HNPP) is a genetic disorder characterized by recurrent focal neuropathies typically occurring at sites of nerve entrapment or compression. It is classically described as a painless condition; however, pain is frequently reported. Due to its rarity and variable clinical presentation, HNPP is often underdiagnosed or initially misdiagnosed. We report the case of a 14-year-old girl who presented with sudden-onset arm weakness and pain following physical activity. The clinical presentation initially raised suspicion for a hereditary demyelinating neuropathy. Although there was no known family history, the patient’s age and the persistence of symptoms supported the hypothesis of a genetic etiology. Neurophysiological studies were consistent with HNPP, which was subsequently confirmed by genetic testing. The primary aim of this report is to emphasize the importance of recognizing the early manifestations of HNPP—including pain, a symptom often underestimated or overlooked—in order to enable prompt diagnosis, reduce unnecessary diagnostic delays, and ensure timely initiation of appropriate genetic counseling. This case supports the notion that pain may represent an early feature of HNPP and should not lead clinicians away from considering this diagnosis.